Investigating the Psychology of Financial Markets During COVID-19 Era: A Case Study of the US and European Markets - Shehzad, Khurram; Xiaoxing, Liu; Arif, Muhammad; Rehman, Khaliq Ur; Ilyas, Muhammad (Frontiers in Psychology, 2020)
Novel coronavirus (COVID-19) has imperatively shaken the behavior of global financial markets. The study estimated the impact of COVID-19 on the behavior of the financial markets of Europe and the US. The results revealed that the returns of the S&P 500 index are greatly affected by the lockdown condition happened owing to COVID-19 in the US. However, the health crisis generated due to novel coronavirus significantly decreased the stock returns of the Nasdaq Composite index. The verdicts also elaborated that the economic crisis generated due to COVID-19 in Spain has more impact on IBEX 35 as compared to the health crisis that resulted in Spain. Besides, in the long-run, Italy's stock markets are more affected by the health crisis as contrasted with the economic crisis, while, in the short-run, both lockdown conditions and economic instability lower the stock returns of FTSE MIB. The UK stock markets witnessed that in the short-run, deficiency of health management system imperatively damaged the stock returns of the London Stock Exchange. The investigation revealed that deficiency of health system and lockdown conditions have imperatively damaged the structure of financial markets, inferring that sustainable development of these nations is at risk due to COVID-19. The study suggested that the government should allocate more budget to the health sector to overcome the health crisis in the future.